2022
DOI: 10.12927/cjnl.2022.26869
|View full text |Cite
|
Sign up to set email alerts
|

Leading Canadian Nurses into the Genomic Era of Healthcare

Abstract: Genomics is having a profound impact on every aspect of healthcare. To support nurses to develop genomic literacy and integrate genomics into care, an engagement framework was created. The framework uses principles of nursing intraprofessional collaboration, the knowledge-to-action cycle and the diffusion of innovations theory. This framework was used to identify six key priorities for action and leadership strategies to accelerate and sustain the nurses' engagement with genomics. With leadership and genomic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Participants in the four studies recognized the importance of GG, however, few indicated they could comfortably apply GG in their practice and the majority demonstrated a lack of foundational GG knowledge. Beyond these studies, other than prior research work conducted by members of our team (Dewell, Seneviratne, et al, 2020;Limoges et al, 2022), there is little research evidence that the integration of GG in nursing practice and education is on the radar in Canada. Furthermore, to our knowledge, there is no Canadian research demonstrating the impact or outcomes associated with GG-informed nursing practice.…”
Section: Genomic Landscape In Canadamentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in the four studies recognized the importance of GG, however, few indicated they could comfortably apply GG in their practice and the majority demonstrated a lack of foundational GG knowledge. Beyond these studies, other than prior research work conducted by members of our team (Dewell, Seneviratne, et al, 2020;Limoges et al, 2022), there is little research evidence that the integration of GG in nursing practice and education is on the radar in Canada. Furthermore, to our knowledge, there is no Canadian research demonstrating the impact or outcomes associated with GG-informed nursing practice.…”
Section: Genomic Landscape In Canadamentioning
confidence: 99%
“…He highlighted the significance of the ‘early adopters’ cohort as a group that is positioned to accelerate the diffusion of an innovation by influencing others who have yet to adopt the innovation. The DOI has been widely used to explore the integration of GG in nursing ( Andrews et al, 2014 ; Calzone et al, 2012 ; Dewell et al, 2021 ; Limoges et al, 2022 ). The key concepts of the DOI are useful to the exploration and analysis of documents as they permitted interpretation of themes within the context of a relevant implementation theory, as well as to build upon the global GG nursing literature informed by the DOI.…”
Section: Background and Purposementioning
confidence: 99%
“…For example, the Canadian Nursing & Genomics initiative is supporting the integration of genomic medicine into nursing practice by considering the role of nurses and engaging nurses in developing a training strategy. 104 Training initiatives in genomics education for health professionals benefits from systems-level support; for example, Genome British Columbia's Genomics Education for Health Professionals Implementation Framework describes promising options that include developing centralized clinical guidelines, point-of-care supporting documents, and professional education that is linked to clinical practice. 105…”
Section: Top Issues About Precision Medicine Technologies To Watch In...mentioning
confidence: 99%
“…The second research paper focused on genomics and nursing by Limoges et al (2022) finds that healthcare, and consequently workplaces, are changing rapidly and leadership is needed to help nurses stay abreast of the changes. Their focus is genomics, a growing component of healthcare that nursing is not keeping up with.…”
Section: Leadership Researchmentioning
confidence: 99%
“…Knowledge of genomics is being actioned in models of care that are tailored to individuals and referred to as precision and personalized healthcare. However, as Limoges et al (2022) observe, Canadian nurses are not being educated about these new models of care and they identify strategies that will rectify this gap.…”
Section: Leadership Researchmentioning
confidence: 99%